THE EPIDEMIOLOGY OF PLASTIC SURGERY CASES IN A TERTIARY GENERAL HOSPITAL IN SURABAYA, INDONESIA - Dwika Intania Riano; Lavonia Berlina Adzalika; Indri Lakhsmi Putri; Rachmaniar Pramanasari (Jurnal Rekonstruksi dan Estetik)
Highlights: